2003
DOI: 10.3109/13813450312331342328
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation, Superoxide Dismutase and Catalase Activities in Brain Tumor Tissues

Abstract: Free radical-mediated damages may play an important role in cancerogenesis. To investigate their relevance in the cancer process, malonyl dialdehyde (MDA) level, superoxide dismutase (SOD), and catalase (CAT) activities were determined in the normal brain tissue and brain tumor tissue. When compared with the normal brain tissue, we have detected: (i) significantly lower MDA concentration in brain tumor tissue (1.63 nmol/mg Pr vs 2.04 nmol/mg Pr; p = 0.03); (ii) SOD activity in brain tumor tissue was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…SOD is an enzyme that catalyzes the dismutation of the superoxide radical (O 2 ·− ) very efficiently ( k 2 ~2 × 10 9  M −1  s −1 ) through a redox reaction of its copper centre enzyme into oxygen (O 2 ) and hydrogen peroxide (H 2 O 2 ). Today, it is clear that decrease of enzymatic activity of the defense system or an overwhelming production of O 2 ·− and/or H 2 O 2 is linked to neurodegenerative disorders (e.g., familial amyotrophic lateral sclerosis [12], AD [13], PD [14], and cancer [15]). The idea that oxygen might not only be involved in the beginning of life and evolution [1618] but also it might be a toxic molecule [19] was further popularized by Halliwell and Gutteridge in their book entitled “Free Radicals in Biology and Medicine” [20] and some important follow-up papers [2123].…”
Section: The Verdict: Oxygen Is Guilty Not Guiltymentioning
confidence: 99%
“…SOD is an enzyme that catalyzes the dismutation of the superoxide radical (O 2 ·− ) very efficiently ( k 2 ~2 × 10 9  M −1  s −1 ) through a redox reaction of its copper centre enzyme into oxygen (O 2 ) and hydrogen peroxide (H 2 O 2 ). Today, it is clear that decrease of enzymatic activity of the defense system or an overwhelming production of O 2 ·− and/or H 2 O 2 is linked to neurodegenerative disorders (e.g., familial amyotrophic lateral sclerosis [12], AD [13], PD [14], and cancer [15]). The idea that oxygen might not only be involved in the beginning of life and evolution [1618] but also it might be a toxic molecule [19] was further popularized by Halliwell and Gutteridge in their book entitled “Free Radicals in Biology and Medicine” [20] and some important follow-up papers [2123].…”
Section: The Verdict: Oxygen Is Guilty Not Guiltymentioning
confidence: 99%
“…Oxidative stress might occur in the background of alteration in optimum levels of trace elements leading to metabolic disorders and changes in cellular structure. Exposure to reactive oxygen species (ROS) can lead to direct DNA damage, mutation, and carcinogenesis [6,7]. Previous studies have reported alterations in the concentrations of serum or neoplastic tissue trace elements in various carcinomas including breast, bladder, gastric, gallbladder, and lung cancers [1,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hyperglycemia-induced oxidative stress is considered the most important factor in TGF-β1 production, which can lead to renal injury and interstitial fibrosis (Forbes et al, 2008). MDA is the end-product of lipid peroxidation and is considered as a marker of oxidative stress (Popov et al, 2003). Our data showed that the production of ROS and MDA were increased in the DM-induced diabetic group, which was accompanied by the impairment of SOD activity, while lovastatin considerably reduced the generation of ROS and MDA, and also it up-regulated the activity of SOD, in addition, lovastatin decreased the expression of NOX4 in the DM-induced diabetic group.…”
Section: Discussionmentioning
confidence: 99%